2019
DOI: 10.3390/su11185002
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Technology Innovation Path Recognition: An Evaluation of Patent Risk of International Trade

Abstract: Patent protection is a critical aspect of sustainable technology innovation, which is currently facing the challenge of patent risk. This study aimed to help enterprises prevent and avoid patent risk in a global view of technology innovation, and to propose a systematic evaluation model for patent risk. By combining the entropy method with the analytic hierarchy process (AHP), this study constructed an analytic hierarchy model of patent risk. Some indexes in the model were selected based on the summary of prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
0
0
Order By: Relevance
“…They found that international companies preferred to have a professional risk manager handle risk management compared to domestic companies. Zhang et al [5] constructed an analytic hierarchy process (AHP) model of patent risk in international trade by combining the entropy weight method with the AHP method. They determined the weight and relative importance of each risk factor based on the assessment results of the AHP method and classified the risk factors as "high", "medium", and "low" according to their priority.…”
Section: Introductionmentioning
confidence: 99%
“…They found that international companies preferred to have a professional risk manager handle risk management compared to domestic companies. Zhang et al [5] constructed an analytic hierarchy process (AHP) model of patent risk in international trade by combining the entropy weight method with the AHP method. They determined the weight and relative importance of each risk factor based on the assessment results of the AHP method and classified the risk factors as "high", "medium", and "low" according to their priority.…”
Section: Introductionmentioning
confidence: 99%